Analyzing the Speech Sound Structures of Indonesian Child Language - Susanto Susanto; Deri Sis Nanda; Chunxu Shi (OKARA: Jurnal Bahasa dan Sastra, 2022)
In the acquisition of language, there could be gradual construction and systematic development of the children's linguistic skills. In their communication, the children speak the words, but their sounds may not be as complete as the adults. This difference between the child and adult language has attracted the attention of scholars in language acquisition to examine if there are specific structures of the child language. This research focuses on the structures of the child's speech sound to see what aspects could explain the difference between child and adult language. The data were the speech of 37 children (Male = 20; Female = 17) with the age range of 1;2 (one year two months) to 5;2 (five years two months). The data was transcribed, and its phonological aspects were classified. PRAAT software (version 6.2.02) was used to study the phonetic properties that support the explanation of the phonological aspects, especially for intensity, duration, and pitch. The study revealed some important aspects of the child language, i.e., syllable deletion, nasal assimilation, velar fronting, lateral substitution, vowel lowering and raising, and pitch harmony. This study may shed new light on the research of speech sound structure for promoting children's literacy programs in Indonesia.